Panel Data Regression Analysis of Human Development Index in West Nusa Tenggara Province with Fixed Effect Model - Sapurah Sapurah; I Gde Ekaputra Gunartha; Nurul Fitriyani (University of Mataram, 2021)
Humans are the true wealth of the nation. It is appropriate if humans become the main goal in development. Then the United Nations Development Program (UNDP) initiated the Human Development Index (HDI) as an indicator in measuring the progress of human development. Indonesia took part in applying the HDI calculation. Increasing the value of HDI from various provinces in Indonesia continues to be carried out, including in the Province of West Nusa Tenggara. Improving human development is based on an increase in all dimensions of the HDI itself. West Nusa Tenggara Province consists of 10 regencies/ cities. With different geographical, social, and economic backgrounds, the achievement of HDI in each region will vary. The purpose of this study was to determine the model of the HDI in West Nusa Tenggara Province in 2010-2017 using a fixed-effect model, which was used to see the influence of dimensions on the HDI and explain the differences in intercepts in each district/ city in West Nusa Tenggara Province. Based on the research conducted, a fixed effect panel data model on HDI was obtained for each district/ city in NTB in 2010-2017. From the HDI model obtained, it is known that the slope coefficient is constant, but the intercept varies throughout the district/ city. The slope coefficient value shows the magnitude of the influence of life expectancy, school duration, the average length of schooling, and expenditure per capita adjusted to the HDI of each district/ city.